Transmission of synthetic seed bacterial communities to radish seedlings: impact on microbiota assembly and plant phenotype - Simonin, Marie; Préveaux, Anne; Marais, Coralie; Garin, Tiffany; Arnault, Gontran; Sarniguet, Alain; Barret, Matthieu (Peer Community Journal, 2023)

(untitled)
Seed-borne microorganisms can be pioneer taxa during germination and seedling emergence. Still, the identity and phenotypic effects of these taxa that constitute a primary inoculum of plant microbiota is mostly unknown. Here, we studied the transmission of bacteria from radish seeds to seedlings using the inoculation of individual seed-borne strains and synthetic communities (SynComs) under  in vitro conditions. The SynComs were composed of highly abundant and prevalent, sub-dominant, or rare bacterial seed taxa. We monitored the transmission of each strain alone or in communities using gyrB gene amplicon sequencing and assessed their impacts on germination and seedling phenotype. All strains and SynComs successfully colonized seedlings and we were able to reconstruct a richness gradient (6, 8 and 12 strains) on both seeds and seedlings. Stenotrophomonas rhizophila became dominant on seedlings of the three SynComs but most strains had variable transmission success (i.e increasing, stable or decreasing during seed to seedling transition) that also depended on the SynCom richness. Most individual strains had no effect on seedling phenotypes, with the exception of Pseudomonas viridiflava and Paenibacillus sp. which had detrimental effects on germination and seedling development. Abnormal seedling morphologies were also observed with SynComs but their proportions decreased at the highest richness level. Interestingly, some bacterial strains previously identified as core taxa of radish seeds (Pseudomonas viridiflava,  Erwinia persicina) were associated with detrimental effects on seedling phenotypes either in isolation or in SynComs. These results confirm that the plant core microbiome includes pathogenic and not only commensal or mutualistic taxa. Altogether, these results show that SynCom inoculation can effectively manipulate seed and seedling microbiota diversity and thus represents a promising tool to better understand the early stages of plant microbiota assembly. This study also highlights strong differences between native seed-borne taxa in the colonization and survival on plant habitats.